Land Contestation in Nepal: Indigenous Land Tenure and National Land Policy - Maharjan, Kabin (New Angle: Nepal Journal of Social Science and Public Policy, 2016)
Current contestations over land as a public or private good revolve around the issue of who owns, controls and manages it. Particularly, after the second April uprising of 2006, indigenous people, have emerged as a new actor in land policy demanding equitable rights for state’s power and resources. However, these claims have been countered by non-indigenous people. The disagreements are strong and the institutional bargaining for a share in land ownership has been tough. Currently, the Ministry of Land Reform and Management is in the process of drafting the National Land Policy. While this draft land policy has addressed the issues of the indigenous people to some extent, the larger approach has been piecemeal and short sighted. If we were to look for a long-term solution, it would be essential to think about major concerns of the marginalized and indigenous group and develop a coherent strategy to address their demand. This paper tries to study and analyze the multiple contestations over land in context of the emergence of indigenous group as an important stakeholder and makes an attempt to come up with a policy option that is rational and far-sighted addressing the multiple intra-group claims.